Dasar-Dasar Manajemen Pesantren - Astuti Astuti; Sukataman Sukataman (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
Management is something that should be applied in various ways, especially in educational Institutions. This article aims to find out about the fundamentals of Islamic Boarding School Management. Management in islmaic educational institutions, one of which is islamic boarding schools, is very important because to be able to regulate, manage and improve all process that occur in islamic boarding schools. The components in the pesantren are kyai, student, book, dormitories, ceregivers, and administrators who work together to achieve common goals. While in management theory themanagement function consists of Planning (Planning), Organizing (Organising), Actuating (Implementation), Controlling (Supervision). With the application of more ideal, dynamic and structured islamic boarding school management, education in islamic boarding school is increasingly advanced and can achieve the goals that have been planned.